Penerapan Analisis Mean dalam Evaluasi Kegunaan Sistem Tes Kemampuan Akademik Calon Mahasiswa Baru Berbasis Use Questionnaire - Tjiptabudi, Fransiskus Mario Hartono (Jurnal Algoritma, 2023)
As an information technology-based tertiary institution, STIKOM Uyelindo Kupang in carrying out all its business processes has implemented various information systems, including the process of admitting new students. In accordance with the standards for the new student admission process, prospective new students must be selected based on the results of academic ability tests. The test is carried out by utilizing an information system to simplify the selection process. This system has been used since 2020 and has made the selection process of prospective new students easier for the campus, but from the perspective of the prospective new students themselves, the level of its usefulness is not yet known so an evaluation is needed to find out this. The evaluation carried out was a usability evaluation based on the USE Questionnaire by applying mean analysis. Data collection involved 267 respondents from system users who were new students in the 2020/2021 to 2022/2023 academic year. The results of the validity test of 30 questionnaire statement items obtained a Sig. (2-tailed) is smaller than the Î± value (0.05) so that all statement items are declared valid, while the Cronbach's alpha value obtained as a result of the reliability test is 0.721, which means it is included in the high reliability category. In addition, for measuring usability, the grand mean value for the usability dimension was 4.62, the ease of use dimension was 4.65, the ease of learning dimension was 4.78, the satisfaction dimension ) is 4.57 and the grand mean value is 4.65 so it is included in the very high category. These results illustrate the positive perception of respondents towards the academic ability test system for prospective new students, where the system is considered very useful and therefore very suitable for use.